Biallelic mutations in EXOC3L2 cause a novel syndrome that affects the brain, kidney and blood. Issue 5 (16th October 2018) - Shalata, Adel; Lauhasurayotin, Supanun; Leibovitz, Zvi; Li, Hongbing; Hebert, Diane; Dhanraj, Santhosh; Hadid, Yarin; Mahroum, Mohammed; Bajar, Jacob; Egenburg, Sandro; Arad, Ayala; Shohat, Mordechai; et al.
Abstract : Background: Dandy-Walker malformation features agenesis/hypoplasia of the cerebellar vermis, cystic dilatation of the fourth ventricle and enlargement of posterior fossa. Although Dandy-Walker malformation is relatively common and several genes were linked to the syndrome, the genetic cause in the majority of cases is unknown. Objective: To identify the mutated gene responsible for Dandy-Walker malformation, kidney disease and bone marrow failure in four patients from two unrelated families. Methods: Medical assessment, sonographic, MRI and pathological studies were used to define phenotype. Chromosomal microarray analysis and whole-exome sequence were performed to unravel the genotype. Results: We report four subjects from two unrelated families with homozygous mutations in the Exocyst Complex Component 3-Like-2 gene ( EXOC3L2 ). EXOC3L2 functions in trafficking of post-Golgi vesicles to the plasma membrane. In the first family a missense mutation in a highly conserved amino acid, p.Leu41Gln, was found in three fetuses; all had severe forms of Dandy-Walker malformation that was detectable by prenatal ultrasonography and confirmed by autopsy. In the second family, the affected child carried a nonsense mutation, p.Arg72*, and no detected protein. He had peritrigonal and cerebellar white matter abnormalities with enlargement of the ventricular trigones, developmental delay, pituitary hypoplasia, severe renal dysplasia and bone marrow failure. Conclusion: We propose that biallelic EXOC3L2 mutations lead to a novel syndrome that affects hindbrain development, kidney and possibly the bone marrow.